Halal Certification Implementation System After The Issuance Of Law Number 33 Of 2014 Concerning Halal Product Assurance In Indonesia - Asman, Asman; Nilhakim, Nilhakim (ASAS, 2024)
The issuance of Law Number 33 of 2014 concerning Halal Product Guarantees is no longer just a discourse but has become part of the state's obligations, by carrying out a substantive function towards Islamic values related to the halal principles in Islam. From the start, it is mandatory to implement halal product guarantees. Government Regulation Number 31 of 2019 which regulates the Implementing Regulations of Law Number 33 of 2014 concerning Halal Product Guarantees, is very good for the existence of BPJPH in carrying out its duties and functions as one of the Halal Product Guarantee Organizing Bodies in Indonesia. under the Ministry of Religious Affairs. This research uses a qualitative descriptive research method where the problem in this research is whether there is an influence of the birth of Law Number 33 of 2014 concerning Halal Product Guarantees regarding the systematics of halal certification. The results of research on the issue of the birth of Law no. 33 of 2014 concerning JPH have no effect on the Cooperation Agreement for LPH candidates with BPJPH regarding the issuance of halal certification.Keywords: Halal Certification; Law No. 13 Of 2014; Halal Product Assurance